Marking Contrastive Topics in a Topic Shift Context: Contrastive Adverbs versus Emphatic Pronouns - Jorina Brysbaert; Karen Lahousse (Discours)
This paper is about two competing marking strategies for contrastive topics in a topic shift context in French: emphatic pronouns and contrastive adverbs. We analyse the choice between these markers in one specific syntactic position, i.e. when they occur between the subject and the finite verb, in different corpora consisting of formal written, informal written and spoken French. Our results indicate that the frequency of emphatic pronouns and contrastive adverbs is register-dependent. Emphatic pronouns appear more often between the subject and the finite verb in the informal written and spoken corpora, whereas contrastive adverbs occur more frequently in this position in the formal newspaper corpora. Moreover, we show that the use of emphatic pronouns is affected by pragmatic constraints, which is not the case for contrastive adverbs: emphatic pronouns typically modify subjects with a clearly identifiable – preferably human – referent. Hence, in a more general way, this study provides evidence for the idea that both language-internal and language-external factors should be taken into account when analysing the “free” choice between two similar linguistic marking strategies.